Mixed-metal metallocavitands: a new approach to tune their electrostatic potentials for controllable selectivity towards substituted benzene derivatives1. Issue 20 (28th May 2015) - Liu, Jian-Jun; Guan, Ying-Fang; Chen, Yong; Lin, Mei-Jin; Huang, Chang-Cang; Dai, Wen-Xin
<x xml:space="preserve">Abstract</x> By integrating two different electronegative metal cations into a metallocavitand, the electrostatic potential of the latter and thus its selective recognition towards the substituted benzene derivatives can be modulated.